Geochemical characterization and artificial thermal maturation of kerogen density fractions from the Eocene Huadian oil shale, NE China. (June 2020) - Xie, Xiaomin; Li, Maowen; Xu, Jin; Snowdon, Lloyd R.; Volkman, John K.
Highlights: Quantitative oil shale maceral concentrates were obtained from an Eocene Huadian oil shale. Density separated maceral groups had different petroleum generation capacities. The properties of end member lamalginite and detrovitrinites properties were determined for maceral isolates. Quantitative retorting behavior can be predicted using precise maceral distributions. Lamalginite generates more hydrocarbons but with a higher activation energy. Abstract: Oil shales are an important alternative energy resource, through retorting, for the production of liquid hydrocarbons. A key factor in determining the value of an oil shale resource is its hydrocarbon generation potential; particularly its maceral distribution. To examine this, single maceral concentrates were obtained from a 1 kg Eocene Huadian oil shale sample using float-sink separation of chemically demineralized kerogen. Nine different density fractions were separated: the Botryococcus fraction occurred in the lightest (<1.06 g/mL) material, lamalginite in the 1.06–1.23 g/mL fraction, while detrovitrinite dominated in a higher density fraction (1.26–1.36 g/mL), which also contained some lamalginite. Rock-Eval S2 and hydrogen index (HI) parameters, as well as the aliphatic compound peaks in Fourier transform infrared (FTIR) spectra, all decreased with increasing kerogen density, whereas the Rock-Eval oxygen index and the aromatic compound peaks in FTIR spectra, increased. The δ 13 C values showed slight variations within the different density fractions. The δ 13 C value of parent shale kerogen was very close to that of the density fraction dominated by lamalginite (−25.1‰), because the sample is dominated by lamalginite macerals (>70%). The Botryococcus sp. fraction is isotopically enriched because Botryococcus sp. is typically significantly enriched in 13 C (δ 13 C = −24.6‰). Artificial thermal maturation hydrocarbon generation results show that absolute hydrocarbon gas yields were similar among the different density fractions. The 1.06–1.12 g/mL fraction, dominated by lamalginite, generated nearly twice as much liquid hydrocarbons as the 1.26–1.30 g/mL fraction dominated by detrovitrinite. The maximum hydrocarbon yields corresponded well with the Rock-Eval HI values. Calculated by the relationships among HI, detrovitrinite and alginite compositions, the HI is 909 and 177 mg HC/g TOC for the purified alginite and detrovitrinite fractions, respectively. Kinetics analysis shows that Ea (activation energy) is higher for the low-density fraction (1.06–1.12 g/mL) than that for the heavy fraction (1.26–1.30 g/mL), indicating that lamalginite not only has a much better hydrocarbon generation potential, but also higher thermal stability. Therefore, this lamalginite-rich oil shale is well suited for exploitation by retorting, even though the retorting temperature would be higher than for detrovitrinite-rich fractions.